2010
DOI: 10.1038/emboj.2010.329
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic engineering shows H3K4me2 is required for HJURP targeting and CENP-A assembly on a synthetic human kinetochore

Abstract: Epigenetic engineering shows H3K4me2 is required for HJURP targeting and CENP-A assembly on a synthetic human kinetochoreHere, centromeric histone marks on a human artificial chromosome are found to resemble the chromatin landscape in transcribed genes, and selective manipulation shows them to govern the incorporation of the centromere-specifying CENP-A histone variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
361
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(383 citation statements)
references
References 62 publications
16
361
4
2
Order By: Relevance
“…While we are gaining a better understanding of the pathway that results in the assembly of CENP-A nucleosomes at centromeres, the precise mechanism for determining the genomic location of CENP-A deposition is unknown. Recent work implicates centromeric transcripts as active participants in CENP-A deposition and centromere function, adding complexity to a pathway previously thought to be restricted to a large protein network (Topp et al 2004;Chueh et al 2009;Ferri et al 2009;Bergmann et al 2011Bergmann et al , 2012. Historically, centromeres were considered simply heterochromatin-rich and thus transcriptionally silent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we are gaining a better understanding of the pathway that results in the assembly of CENP-A nucleosomes at centromeres, the precise mechanism for determining the genomic location of CENP-A deposition is unknown. Recent work implicates centromeric transcripts as active participants in CENP-A deposition and centromere function, adding complexity to a pathway previously thought to be restricted to a large protein network (Topp et al 2004;Chueh et al 2009;Ferri et al 2009;Bergmann et al 2011Bergmann et al , 2012. Historically, centromeres were considered simply heterochromatin-rich and thus transcriptionally silent.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, transcripts emanating from both the pericentromere and centromere core have been identified in a multitude of organisms (Eymery et al 2009a;Stimpson and Sullivan 2010). Moreover, recent studies have identified proteins that interact with these transcripts (Topp et al 2004;Wong et al 2007;Chueh et al 2009;Ferri et al 2009;Du et al 2010;Hsieh et al 2011), analyzed the effects of increased and decreased transcription on genome stability (Bergmann et al 2011;Ohkuni and Kitagawa 2011;Bergmann et al 2012), or identified changes in transcription in stressed or diseased cells (Eymery et al 2009b;Gopalakrishnan et al 2009;Ting et al 2011;Zhu et al 2011). In this review, we will present pericentric and centromeric noncoding RNA transcription and discuss its diverse roles in modified histone recruitment, centromere function and stability, and insulator activity as well as newly discovered correlations between centromere and pericentromere transcription and human disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diminished levels of H3K4 methylation affects the recruitment and deposition of the histone CENPA at centromeres of human artificial chromosomes, providing direct evidence for the involvement of Set1-mediated methylation in kinetochore function (Bergmann et al 2011). Therefore misregulation of centromere-kinetochore functions could contribute to the synthetic lethality and SAC-monitored mitotic defects in cells lacking adequate NIMA and Set1 complex function.…”
Section: Set1 Complex Function Is Required With Nima For Normal Transmentioning
confidence: 99%
“…In addition, H3K4 methylation is also involved in maintaining the repression of telomere proximal genes in S. cerevisiae and Schizosaccharomyces pombe and the suppression of secondary metabolite production in A. nidulans and A. fumigatus (Krogan et al 2002;Kanoh et al 2003;Bok et al 2009;Palmer et al 2013). Growing evidence indicates that the Set1 complex is involved in a gamut of additional cellular functions, many of which may be independent of its roles in gene expression, including kinetochore maintenance, DNA repair, and replication checkpoints (Faucher and Wellinger 2010;Bergmann et al 2011). Importantly the Set1 complex regulates mitosis in budding yeast with the Aurora mitotic kinase Ipl1 and the type1 phosphatase Glc7 (Zhang et al 2005;Latham et al 2011).…”
mentioning
confidence: 99%